Economic Digitalization in an Effort to Maintain Family Economic Resilience Based on Local Wisdom - Windianingsih, Agustin; Yunas, Muhammad Faisal; Farhani, Hilma (Formosa Journal of Applied Sciences, 2024)
The uniqueness of the Baduy tribe is a special attraction for local, national and international tourists. The Baduy tribe has a very close relationship with local wisdom which has been passed down from generation to generation. This research is a type of literature study research with a descriptive approach, namely collecting data and information from the Baduy tribe community and various literature from various sources. Several obstacles identified as causing the slow progress of Baduy SMEs include first, limited access to digital technology. Second, digital literacy is still low among Baduy SMEs. Third, language and cultural barriers in understanding the language of the digital economy, fourth, obstacles to the lack of access to financial sources, and fifth, there is still low access and reach of digital marketing for Baduy products.